Rhythmic Auditory Stimulation in Gymnastics Learning: Enhancing Movement Creativity in Primary School Gymnastics Through Music-Based Pedagogy - Muhamad Gumelar Asmarandana At Thaariq; Tedi Supriyadi; Aam Ali Rahman (Tadulako Journal Sport Sciences And Physical Education, 2026)
Physical education in elementary schools often focuses on a mechanical and repetitive approach, particularly in gymnastics, which limits originality and fluency in developing movement creativity. This study was conducted at Prapatan Elementary School in Majalengka to test the effectiveness of the Rhythmic Auditory Simulation (RAS) intervention in enhancing student creativity through music-based pedagogy. This study used a one-group pretest-posttest experiment by isolating the direct impact of external stimulation on a homogeneous group of subjects. To ensure internal validity, the research design was strengthened through constant control of audio tempo standardization and the elimination of visual instructions from the teacher. The results of data processing showed an average N-Gain score of 35%, indicating a statistically significant increase in motor creativity despite limited intervention effectiveness. Due to the limited effectiveness, this indicates that internal constraints in the form of students' biological motor skills in middle childhood and the short duration of the intervention, which was 3 weeks, caused the limited intervention. This study contributes by proving the function of external audio rhythmic structures as action opportunities through an ecological dynamics paradigm that is able to manipulate children's kinetic movement space while simultaneously building a sense of psychological safety during activities. This research offers a physical education curriculum model with a measurable motor behavior control instrument through the placement of music so that music plays a role not just as a background to create a classroom atmosphere.